Effectiveness of erosion control structures in reducing soil loss on skid trails - Solgi, Ahmad (Array, 2021)
Forest operations can lead to increased runoff and soil loss on roads and skid trails. Best management practices (BMPs) aim to minimize erosion and water quality problems, but the efficacies of various BMP options such as water bars are not well documented. The aim of this study was to evaluate the effects of different densities of water diversion structures (water bars) on runoff volume and soil loss on different skid trail gradients on two soils with different textures in the Shenrood forest, Guilan province, northern Iran. The treatments included combinations of four densities of water bars (1, 2, 3 or 6 water bars per 150 m length of skid trail section [overland trail]), on two levels of trail gradient (≤20% and >20%) and two soil textures (clay loam and silt loam). Average runoff volume and soil loss per m2 of skid trail surface area were significantly greater (P≤0.05) on silt loam than on clay loam textured soils, and on slope gradients >20% (23–28%) than on gradients ≤20% (5–13%). Average runoff volume increased, and average soil loss decreased significantly (P≤0.05) with increasing density of water bars on both gradients and on both soil textures. On both soil textures, the lowest surface runoff volumes were observed with one water bar and the greatest volumes with six water bars installed. In contrast, the smallest amount of soil loss on both soil textures was observed with six water bars, and the greatest soil loss when only one water bar was installed. The installation of additional water bars led to significant differences in both responses at each level of density and led to reductions in soil loss of 77%, 57% and 27% in the clay loam, and 79%, 60% and 30% in the silt loam soil compared to the single water bar treatment. The reduced soil loss per unit of surface runoff volume is likely due to the reduced velocity of surface water runoff in the skid trail.